The Political aspects of Kazakh-Turkish Relations (1991-2007) - Aмирбек A.A; Сериккaлиевa A.Е (Journal of Oriental Studies, 2024)
In twenty five years, the Kazakh-Turkish political relations have grown into a strategic partnership. The strategic partnership is based on a stable political relations. In this context, it is important to not be limited to the classical concept of the alliance, but rather to analyze the political partnership between the two countries on the basis of a much deeper and more critical concept of partnership. First of all, Kazakhstan and Turkey share common historical roots and culture. This has contributed to a correct understanding of mutual political interests of the two countries and enhancement of the relationship to the level of a strategic partnership. Currently, both countries are strengthening the strategic partnership, basing many issues in the Eurasian region on common political principles. Key words: Kazakhstan, Turkey, Russia, multilateral foreign policy, strategic partnership.